Four storms with sub-events: Sampling and analysis - AKKOYUNLU, BÜLENT OKTAY; TAYANÇ, METE (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Analysis of ion concentration of samples taken sequentially during a storm event is important in order to reveal the relation between the atmospheric conditions and ion concentrations in each sub-event. This study presents the interrelationship among the chemical composition parameters and atmospheric variables for four storm events that were sampled in Istanbul during a) January 21-23, 2004 b) November 9-11, 2003 c) February 12-13, 2004 and d) October 27-28, 2003. These events lasted 53.3, 47.9, 27.5 and 13.2 h and the number of collected samples for each event was 22, 14, 7 and 4, in order. Generally values of pH and concentrations of ions in the first sub-events for all four cases were found higher than those of the other sub-event samples taken in sequence owing to the strong initial washout of the atmosphere by raindrops. Precipitation events a and c include rain and snow together where precipitation started as rain and continued as snow after 16th and 3rd sub-events. Higher concentration of ions in the snow in comparison with that of rain sub-events samples can be explained by more efficient below cloud scavenging of atmospheric constituents, especially aerosol particles, by snowflakes. In general, all of the ions sampled in the sub-events for four storms have variability similar to each other, with high correlation coefficient among themselves. Cl- and SO42- were found to be the dominant domestic emissions, most of the Ca2+ and K+ came from soil, nearly half of the Mg2+ and all of the Cl- originated from sea. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: acid precipitation; sub-event analysis; rain chemistry; CHEMICAL-COMPOSITION; PRECIPITATION; DEPOSITION; WET; CHEMISTRY; RAINWATER; ISTANBUL; FOREST; TURKEY; RAIN